Stress, adaptive coping, and resilience of nursing students in South Kalimantan, Indonesia - Dias, Maria Frani Ayu Andari (2023)
Stress in an unavoidable condition even for nursing students; however, if not managed effectively, it has negative implications to academic performance and mental health. Assessing nursing students’ stress, resilience, and adaptive coping can be a basis to redesign nursing curriculum and an educational environment conducive for promotion of optimal competence and mental health. -- The purpose of this study was to explore and analyse information that can guide the development of a school mental health program for nursing students in South Kalimantan, Indonesia. This includes describing the level of stress, adaptive coping and resilience of nursing students and relate these to their academic and sociodemographic characteristics. The study also analysed the interrelationship of adaptive coping and resilience of nursing students with their stress level. -- The study used descriptive-correlational design covering six nursing colleges of South Kalimantan, Indonesia. Quota sampling based on type of school, nursing program, and year level of study was used in the recruitment of 395 nursing students. In addition to the sociodemographic and educational questionnaires, three validated questionnaires were used: Student-life stress inventory (SSI), How Resilient are you (HRAY), and Coping Adaptation Processing Scale (CAPS). -- Data were analysed using Jamovi version 1.8.1 to perform descriptive data analysis, student t-test, ANOVA, chi-square statistic, and correlations. -- Result showed that although most (67%) of the respondents had low levels of stress, and 89% reported low reaction to stress (66.2 18.4), it is concerning to have 33% of the students with high levels of stress (73.9 9.10). Note that data was collected during the COVID-19 pandemic that also hit Indonesia. -- Sources of stress identified in the study were categorized into personal, social, academic and clinical experiences. Significant sources of stress included desire to discover the perfect answer to the difficulties they face (M=3.46, SD=1.20), the need to be cared for and loved by everyone (M=3.31, SD=1.34), and a preoccupation with everything and everybody (M=3.31, SD=1.12). Personal stressors reported by Nursing students were insufficient source of educational support (M=2.93, SD=0.956), social stressors were courses which being complicated for students to understand (M=2.59, SD=0.830) and clinical stressors appeared when they were underappreciated and got marks by trainer in clinical practice (M=2.70, SD=0.929). -- Academic variables that were significantly related to level of stress were as follows: type of school with STIKES students having higher stress level (p=0.006), and type of nursing program (p<0.001), mostly BSN students. There were few personal and social characteristics related to stress: gender (p<0.001), ethics group (p=0.017), and financial status measured as working status of students (P<0.001) and source of educational support (p<0.001). Working students had a higher stress level (64.3 15.1). This finding of financial status was expected. Working students were mostly diploma graduates, already working full time, and studying on the weekends to complete a BSN degree. -- Regarding adaptive coping of students, almost all (91.39%) had moderate capacity coping (41.3 10.9). Adaptive coping were also related to the same factors of stress of type of school (p<0.05), gender (p<0.001), ethical group (p<0.001), and working status (p<0.001) and sources of educational support (p<0.001). Unlike stress, religion was a factor of student adaptive coping (p<0.001) with Christians (Roman Catholic, Protestant) having the highest score in adaptive coping (45.4 7.91). -- For resilience of the student respondents, 42.28% of nursing student had middle-low resilience (60.4 18.7) and 4.04% had low resilience. This result infers that almost half of the nursing students have limited resiliency skills and ability dealing with stress and may need interventions to enhance resilience. -- Variables that were shown to relate significantly with student resilience were nursing program (p<0.001), gender(p<0.001), religion (p<0.001), ethnic group (p<0.001), working status (p<0.001) and source of educational support (p<0.001). Gender, mostly females, and religion, mostly the christian students, seemed to have higher resilience levels and may have modulated the actual and perceived stress. -- To determine interrelationship of the main variables of stress level, adaptive coping and resilience, Spearman’s rank correlation was analysed. Results showed that overall adaptive coping of students had a positive and moderate relationship with their stress level (r=0.371, p<.001). Similarly, overall resilience and stress level of nursing students had a positive but weaker relationship (r=0.294, p<.001). -- Several factors shown in this thesis may contribute to student mental health, adaptive coping and resilience which should be carefully considered by school administrators and educators. In particular, these results can help identify students who may need support to enhance resilience. Some curricular measures may be considered to minimise academic stress. It is imperative that school-based mental programs be developed and tailored to students needs as part of their overall holistic development.